Electroconvulsive therapy for an older patient with schizophrenia complicated by nonconvulsive status epilepticus during catatonia: A case report - Ayumi Takeshita; Masaya Mashimoto; Hiromi Chiba; Motohiro Ozone (PCN Reports, 2025)
Abstract Background Nonconvulsive status epilepticus (NCSE) can present with symptoms resembling catatonia, such as stupor, staring, and immobility. Distinguishing between the two conditions using electroencephalography (EEG) is crucial. However, reports of NCSE coexisting with catatonia are rare. Case Presentation We present a case of catatonia associated with schizophrenia complicated by NCSE. A 77‐year‐old woman with a 30‐year history of well‐controlled schizophrenia developed stupor and was admitted to our hospital. EEG revealed evolving spike‐and‐wave complexes, leading to a diagnosis of NCSE. Administration of levetiracetam improved the EEG findings, and subsequent monitoring confirmed resolution of epileptiform activity. However, the patient's stuporous state persisted despite the normalized EEG. Extensive workup showed no evidence of encephalitis or other neurological pathology. We diagnosed her with NCSE and catatonia associated with schizophrenia. Electroconvulsive therapy (ECT) was administered, resulting in complete resolution of the catatonic symptoms. Conclusion This case highlights three key points. First, stupor can result from both NCSE and catatonia associated with schizophrenia. Second, when no physical cause for NCSE is identified and symptoms persist despite EEG improvement following antiepileptic treatment, coexisting catatonia associated with schizophrenia should be considered. Finally, ECT was effective in treating catatonia associated with schizophrenia complicated by NCSE. In patients presenting with stupor, it is important to differentiate between NCSE and catatonia associated with schizophrenia and to recognize the potential for their coexistence.